Heart failure secondary to a snake bite. The intensivist's vision: case report: Insuficiencia cardíaca secundaria a mordedura de serpiente. La visión del intensivista: reporte de caso - Restrepo Bastidas, Andrés Alirio (2024)
Background: Ophidic accident is a neglected disease that affects tropical countries. Latin America is the second region after Africa, with the most cases worldwide. Local lesions accompany its clinical course up to systemic affectations such as renal, hematological, and neurological lesions. Cardiac complications are rare, especially in patients who do not have cardiovascular risk factors. There are reports of acute myocardial infarction, but there is little information about heart failure due to Bothrops spp. Case report: We present the case of a 25-year-old man without cardiovascular risk factors who was admitted to the intensive care unit and developed heart failure with cardiogenic shock and multi-organ failure secondary to a snake bite. Conclusions: Although the characteristic clinical course of a bothropic ophidian accident and its systemic manifestations are mainly related to coagulation abnormalities, there are cardiovascular complications within its clinical presentation that, although rare, if not detected promptly and not adequately managed, are associated with high morbidity and mortality.